NURTURING A ROBUST DIGITAL FOOTPRINT: ORCHESTRATING TACTICAL MASTERY IN THE REALM OF ONLINE MARKETING EXCELLENCE - Euis Eka pramiarsih; Sri Mulyono; Loso Judijanto; Hurulaini Sekar Azzahra; Antono Damayanto (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The relentless evolution of the digital landscape has propelled online marketing to the forefront of strategic business initiatives. This study explores the multifaceted journey of "Nurturing a Robust Digital Footprint," delving into strategic planning, social media dynamics, technological innovations, user experience, measuring digital success, storytelling, agility, adaptability, ethical considerations, and collaborative partnerships. The synthesis of these insights offers businesses a comprehensive guide to achieving excellence in online marketing. From formulating intentional strategies to embracing technological innovations, prioritizing user experience, and navigating ethical considerations, companies are equipped with the tactical mastery required to orchestrate a robust digital footprint. The study culminates in a call to action for businesses to navigate the dynamic digital realm with authenticity, innovation, and ethical responsibility, shaping a digital footprint that resonates with contemporary consumers.